2007
DOI: 10.1111/j.1476-5829.2007.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of plasma DNA as a prognostic indicator in canine lymphoid neoplasia

Abstract: Dogs have a similar incidence of spontaneous cancers as people, and a noninvasive test to monitor disease status in dogs would be of great value. Humans with cancer often have increased levels of cell-free circulating DNA in their plasma, which has shown promise for diagnosis, prognosis and detection of residual disease. We hypothesized that dogs with cancer have increased circulating DNA compared with healthy dogs or dogs with non-neoplastic diseases. Plasma DNA was measured in 40 healthy dogs, 20 dogs with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 41 publications
(98 reference statements)
7
43
1
Order By: Relevance
“…In the present paper, cfDNA was analyzed without DNA extraction, thus, eliminating the loss of small DNA fragments in the extraction process. Using the technique described in this manuscript, the lowest concentration of cfDNA was 439 ug/L, whilst the range of concentrations reported by Schaefer et al (2007) was 1-91 ug/L, which was similar to the experimental data reported by Uzuelli et al (2009), and in both studies, DNA extraction was performed with QIAmp DNA blood mini Kits, prior to DNA quantification. Standard DNA extraction protocols are extremely insensitive at conserving small DNA fragments (<100 bp), resulting in up to eight-fold variations in the human literature in cfDNA concentrations when DNA extraction was performed using standard extraction techniques (Jung et al 2010).…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…In the present paper, cfDNA was analyzed without DNA extraction, thus, eliminating the loss of small DNA fragments in the extraction process. Using the technique described in this manuscript, the lowest concentration of cfDNA was 439 ug/L, whilst the range of concentrations reported by Schaefer et al (2007) was 1-91 ug/L, which was similar to the experimental data reported by Uzuelli et al (2009), and in both studies, DNA extraction was performed with QIAmp DNA blood mini Kits, prior to DNA quantification. Standard DNA extraction protocols are extremely insensitive at conserving small DNA fragments (<100 bp), resulting in up to eight-fold variations in the human literature in cfDNA concentrations when DNA extraction was performed using standard extraction techniques (Jung et al 2010).…”
Section: Discussionsupporting
confidence: 61%
“…The concentration of cfDNA was increased in dogs with both neoplastic and non-neoplastic diseases. This contrasts with the findings of Schaefer et al (2007), who reported that the cfDNA concentration was only elevated in dogs with lymphoma (Schaefer et al 2007). It is most likely that the contrast is due to the difference in sample handling between the two studies.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations